STRESS AND TECHNIQUES OF OVERCOMING MENTAL STRESS - Enes Huseinagić; Adnan Hodzić (Sport Scientific And Practical Aspects, 2025)
It is often difficult to excommunicate stressful situations. Therefore, people are forced to confront then and to try to overcome them. Strategies of confronting and overcoming stress differ. Naturally, it is very good to know types of stress, both physical and mental, on which an individual can easily react. When a person realises that the situation can be controlled successfully, and that active i.e. problem focused strategies can be used, stress consequences are greatly annulled. The worst thing a person can do is to try and avoid confronting stress, which has a long-term consequence of increasing stress and developing an illness. Almost all authors, experts who deal with this problem, have a shared opinion that, in transitional countries, a synchronisation of Law on work protection with basic guidelines of EU as well as articulating the problem of stress at work and its impacts is yet to come. Problem needs to be dealt with multi- disciplinary measures, including joined activities of doctors, work psychologists, clinical psychologists, educated staff and sport staff.